Granulosa cells apoptosis and follicular fluid hormones: comparison of progestin-primed ovarian stimulation versus GnRH antagonist protocols. (3rd July 2021) - Li, Xiaolan; Zhang, Xiaoli; Cai, Jiawei; Pang, Jiahui; Sun, Peng; Chen, Jianhui; Wang, Meng; Liang, Xiaoyan
Abstract: Objective: To explore the effect of progestin-primed ovarian stimulation protocol (PPOS) on mural granulosa cells (GCs) apoptosis and hormonal profiles in follicular fluid (FF) and efficacy over GnRH antagonist (GnRH-A) protocols. Methods: We performed a prospective cohort study from June through August 2017 at a tertiary teaching hospital. 63 Patients meeting our criteria were recruited in this prospective study voluntarily and stratified to PPOS or GnRH-A group randomly. Mural GCs and FF were collected during oocyte retrieval. Apoptosis of GCs was assessed using the Annexin V-affinity assay by flow cytometry and hormonal profiles in FF were measured using electrochemiluminescence. Results: A total of 63 women were assessed for eligibility, with 25 cases in PPOS group and 38 in GnRH-A group. Difference of early stage apoptosis rate, late stage apoptosis rate, and total apoptosis rate did not reach statistical significance between groups. Meanwhile, concentrations of hormones in FF were comparable in two groups. No statistically significant differences were observed in number of oocytes retrieved, mature oocyte rate, fertilization rate, and top-quality embryos rate. No patients experienced premature LH surge in both groups during the study. Conclusion: Compared to GnRH antagonist protocol, PPOS had comparable laboratory outcomes, GCs apoptosis rate and hormonal profiles in FF. PPOS is an effective and safe alternative option to provide controlled ovarian hyperstimulation (COH).